China and Central and Eastern European Countries : Regional Networks, Global Supply Chain, or International Competitors? - Fung, K.C.; Korhonen, Iikka; Li, Ke; Ng, Francis (World Bank, Washington, DC, 2012)
China has emerged as one of the top recipients of foreign direct investment in the world. Meanwhile, the successful transition experience of many Central and Eastern European countries has also allowed them to attract an increasing share of global foreign direct investment. In this paper, the authors use a panel data set to investigate whether foreign direct investment flows to these two regions are complements, substitutes, or independent of each other. Taking into account the role of host country characteristics - such as market size, degree of trade liberalization, and human capital - the authors find no evidence that foreign direct investment flows to one region are at the expense of those to the other. Instead, the results suggest that foreign direct investment flows are driven by distinct regional production networks (and thus are largely independent of each other) and the development of global supply chains (indicating that foreign direct investment flows are complementary).